The Non-party Caretaker Government (NCG) for conducting elections: Bangladesh as a case study - Quddus, S. M. Abdul; Quddusi, Kazi S. M. K. Alam (2011)

(untitled)
This paper is based on empirical data collected mainly from published secondary sources, personal observation of national election as well as information from the EC website and print and electronic media about election and democracy in Bangladesh. The paper argues that Bangladesh democracy is again at the crossroads as the provision of Non-party Caretaker Government (NCG) has been scrapped from the Constitution despite resistance from the main opposition block. In fact, even after restoration of democracy in 1991, democracy has been provided with little room for expected development by uncouth electoral politics. Though an interim arrangement, called Caretaker System, was introduced for transition from dictatorship into democracy in 1991, the system had to be continued due to distrust of elections under party governments. Three consecutive Caretaker Governments were relatively successful in holding free and fair elections. However, the fourth one suffered a setback owing to composition imbroglio and was replaced by a military-backed Caretaker Government. Therefore, this paper draws the conclusion that though electoral system under Non-Party Caretaker Government system achieved kind of stability during the last four general elections but little qualitative change has taken place in the country’s political arena.